Berberine attenuates pulmonary arterial hypertension via protein phosphatase 2A signaling pathway both in vivo and in vitro. Issue 12 (5th August 2018) - Luo, Jie; Gu, Yue; Liu, Pengfei; Jiang, Xiaomin; Yu, Wande; Ye, Peng; Chao, Yuelin; Yang, Hongfeng; Zhu, Linlin; Zhou, Ling; Chen, Shaoliang
Abstract : Excessive proliferation, migration, and antiapoptosis of pulmonary artery (PA) smooth muscle cells (PASMCs) underlies the development of pulmonary vascular remodeling. The innervation of the PA is predominantly sympathetic, and increased levels of circulating catecholamines have been detected in pulmonary arterial hypertension (PAH), suggesting that neurotransmitters released by sympathetic overactivation may play an essential role in PAH. However, the responsible mechanism remains unclear. Here, to investigate the effects of norepinephrine (NE) on PASMCs and the related mechanism, we used 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2‐ H ‐tetrazolium bromide, the proliferating cell nuclear antigen and the cell counting kit‐8 assay to evaluate the proliferation of PASMCs, Boyden chamber migration, and wound‐healing assays to assess migration and western blot analysis to investigate protein expression. We demonstrated that the phosphorylation level of the protein phosphatase 2A (PP2A) catalytic subunit (Y307) was higher in PAH patients and PAH models than in controls, both in vivo and in vitro. In addition, NE induced the proliferation and migration of PASMCs, which was attenuated by berberine (BBR), a Chinese herbal medicine, and/or PP2A overexpression. PP2A inhibition worsened NE‐induced PAH and could not be reversed by BBR. Thus, PP2A is critical in driving PAH, and BBR may alleviate PAH via PP2A signaling pathways, thereby offering a potential therapeutic option for PAH. Abstract : Our study indicated that protein phosphatase 2A was an essential regulator in pulmonary artery smooth muscle cells (PASMCs) and provided evidence supporting the potential of berberine in inhibiting the migration and proliferation of PASMCs.